If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24x-22=-5(1-6x
We move all terms to the left:
24x-22-(-5(1-6x)=0
We add all the numbers together, and all the variables
24x-(-5(-6x+1)-22=0
| 5n+1=3;+7 | | X²-20x-21=0 | | 19.95+85x=184.85 | | -4n-5+n=7(7-7n)=6(1+6n) | | x2+2x=4 | | 3u/7=-15 | | (3x-6)(9x+6)=0 | | 3x^2+92x=-9 | | -46=-v/3 | | 6x+35=7x+16 | | 75+3x-3=90 | | x2+12x=6 | | 3-4(x-2)=-2x-7 | | 36x+31=535 | | v=3.148(2)5 | | Y=4x^2+x-1 | | (3x+1)x(2x+1)=8 | | X-0.2x=260. | | 3x+15=3+4x | | 45-4x=19+9x | | 4(x-2)=x=10 | | 3x10x6=60 | | 180=-3(-4-7x | | x2-6x=5=0 | | 1.5-a=5.25 | | 1/3x2-2x=9 | | -7(9-2x)=137-11x | | 13x2−2x=9. | | x+1=x+12 | | (-12x+3)+(5x-9)=0 | | 13x2−2x=9 | | 4^2=-4x-1 |